(3JYdjb GdMeGFd ajeG CZadg TQGM GdTeGFds - (3CHh YHO Gddg Hf WGgQ Hf Me GdcQSjaj GdJGRjs
(3ChdgG (B:s
(3LeY ajg eG GaJQb ai ZjQg , hGSJNdag hGSWI Hjfg hHjf Ndbg s
(3BNQgG (B:s
(3hef cGfJ gLQJg Edi OfjG jUjHgG Ch GeQCI jfcMgG agLQJg Edi eGgGLQ Edjg , afSCdg Cf jLYdg ef PNGFQ GdYbHi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B116 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(934 (3c(B) s
Keywords: (3GdWHs